Combination of Nanomaterials in Cell-Based Drug Delivery Systems for Cancer Treatment - Lu Tang (MDPI AG, 2021)
Cell-based drug delivery systems have shown tremendous advantages in cancer treatment due to their distinctive properties. For instance, delivery of therapeutics using tumor-tropic cells like neutrophils, lymphocytes and mesenchymal stem cells can achieve specific tumor targeting due to the “Trojan Horse” effect. Other circulatory cells like erythrocytes and platelets can greatly improve the circulation time of nanoparticles due to their innate long circulation property. Adipocytes, especially cancer-associated adipocytes, play key roles in tumor development and metabolism, therefore, adipocytes are regarded as promising bio-derived nanoplatforms for anticancer targeted drug delivery. Nanomaterials are important participants in cell-based drug delivery because of their unique physicochemical characteristics. Therefore, the integration of various nanomaterials with different cell types will endow the constructed delivery systems with many attractive properties due to the merits of both. In this review, a number of strategies based on nanomaterial-involved cell-mediated drug delivery systems for cancer treatment will be summarized. This review discusses how nanomaterials can be a benefit to cell-based therapies and how cell-derived carriers overcome the limitations of nanomaterials, which highlights recent advancements and specific biomedical applications based on nanomaterial-mediated, cell-based drug delivery systems.